Sunstein, Cass R. Decisions about Decisions: Practical Reason in Ordinary Life - Luca, Michael (Journal of Economic Literature, 2025)
Michael Luca of Johns Hopkins University reviews “Decisions about Decisions: Practical Reason in Ordinary Life” by Cass R. Sunstein. The Econlit abstract of this book begins: “Explores the psychological, practical, and emotional factors that inform decision-making processes.”